Ari G. Agaom Analisis SWOT untuk Pengembangan Program Bursa Kerja Khusus di SMK Negeri 3 Bengkulu Selatan: Meningkatkan Daya Saing Lulusan melalui Optimalisasi Bursa Kerja Khusus - Gunawan, Ari; Danim, Sudarwan (Manajer Pendididikan, 2025)
This study analyzes the development strategy of the Special Job Placement Program (BKK) at SMK Negeri 3 Bengkulu Selatan using the SWOT method. The analysis shows that the program’s strengths lie in its qualified human resources, industry-based curriculum, strong business collaborations, and supporting facilities like the E-BKK Online platform. However, weaknesses remain, such as limited administrator training, a shortage of industry-certified teachers, and inadequate industrial-standard facilities. Opportunities include industrial growth, government policy support, and rising demand for skilled vocational graduates. Meanwhile, the program faces threats such as rapid technological changes, bureaucratic hurdles, limited funding, and competition from other schools. To optimize the program, it is crucial to leverage strengths and opportunities by maximizing the E-BKK platform, enhancing industry partnerships, updating curricula, upgrading facilities, and providing continuous human resource training. Regular evaluation and policy improvements are essential to maintain graduates' competitiveness. The BKK program plays a vital role in bridging graduates to the workforce, reducing unemployment, fostering entrepreneurship, and supporting economic development at both local and national levels.